Working-class entrepreneurialism: Perceptions, aspirations, and experiences of petty entrepreneurship among male manual workers in Turkey. (November 2019) - Birelma, Alpkan
Abstract: This article examines working-class entrepreneurialism in Turkey from a comparative perspective. Based on ethnographic fieldwork conducted in a working-class neighborhood of İstanbul, the article focuses on the perceptions, aspirations, and entrepreneurial attempts of manual workers employed in formal jobs. It aims to contribute to the understudied literature on working-class entrepreneurialism, which is often overlooked or underestimated by the critical research on labor and the working class. First, the article demonstrates that the level of entrepreneurialism among manual workers is rather high. Alongside revealing the popularity of aspirations for self-employment and the working-class roots of many self-employed individuals, I present an ethnographic account of five workers' transition from wage work to self-employment. Second, the article finds that a colloquial phrase, " el işi " or "a stranger's business, " is widely used to refer to wage work. I argue that this phrase perfectly manifests the popular resentment felt toward wage labor in a social milieu where self-employment seems accessible. Finally, by drawing on a review of a scattered set of studies, I claim that entrepreneurialism among working-class men seems to be quite common, especially in peripheral countries.